The generosity crisis : the case for radical connection to solve humanity's greatest challenges - Chappell, Nathan; Crimmins, Brian; Ashley, Michael (John Wiley & Sons, Inc., 2023)
"...Accomplished philanthropy experts Nathan Chappell, Brian Crimmins, and Michael Ashley deliver a startlingly insightful exploration of the decline of American generosity. The authors offer inspirational solutions to the dramatic downturn in giving in the US, showing us how to re-establish the interconnection that drives reciprocity, love, and generosity. You'll discover how to help reignite the radical connection between us and value-driven organizations that strive to improve life on Earth. You'll also become part of the conversation about generosity as an antidote to isolation and learn to take personal responsibility for the world's most seemingly intractable problems"--